Motivasi Mahasiswa dalam Mengikuti Program Internship di Jepang - Muthiarawaty Muthiarawaty; Soni Mulyawan Setiana (Program Studi Sastra Jepang, Universitas Komputer Indonesia Bandung, 2022)
Abstract This study aims to determine the motivation or interest of students in participating in the internship program in Japan. This research was conducted using a quantitative descriptive method. Data was collected by distributing questionnaires to active students of the Japanese language/literature study program from four universities in the city of Bandung. The results showed that most of the students had high motivation and interest in participating in the internship program in Japan. Internship programs that students want to participate in themselves, exist in various fields of work such as golf, restaurants, or hospitality. However, there are several factors that need to be considered by students when they want to join the internship program. So that students can take part in the internship program well, students need to be equipped with Japanese language skills that are equivalent to N3, so that later language will not be an obstacle and students can communicate and carry out their internship program smoothly and well. Therefore, the Study Program should hold special classes for students who are interested in participating in an internship program according to their field. Keywords: Japanese department; motivation; student internship Abstrak Penelitian ini bertujuan untuk mengetahui motivasi atau minat mahasiswa dalam mengikuti program internship di negara Jepang. Penelitian ini dilakukan dengan menggunakan metode deskriptif kuantitatif. Pengumpulan data dilakukan dengan cara menyebarkan angket kepada mahasiswa aktif program studi bahasa/sastra Jepang dari empat Universitas di kota Bandung. Hasil penelitian menunjukkan bahwa sebagian besar mahasiswa memiliki motivasi dan minat yang tinggi untuk mengikuti program internship di Jepang. Program internship yang ingin diikuti oleh mahasiswa sendiri, ada dalam berbagai bidang pekerjaan seperti golf, restoran, ataupun perhotelan. Hanya saja, ada beberapa factor yang perlu diperhatikan oleh mahasiswa ketika ingin mengikuti program internship. Agar mahasiswa dapat mengikuti program internship dengan baik, mahasiswa perlu dibekali dengan kemampuan Bahasa Jepang yang setara dengan N3, sehingga nantinya Bahasa tidak menjadi kendala dan mahasiswa dapat berkomunikasi serta menjalani program internshipnya dengan lancar dan baik.. Oleh karena itu Program Studi sebaiknya mengadakan kelas khusus bagi mahasiswa yang tertarik mengikuti program internship sesuai bidangnya. Kata Kunci: Departemen bahasa Jepang; magang mahasiswa; motivasi